2020
DOI: 10.1090/mcom/3529
|View full text |Cite
|
Sign up to set email alerts
|

Computational high frequency scattering from high-contrast heterogeneous media

Abstract: This article considers the computational (acoustic) wave propagation in strongly heterogeneous structures beyond the assumption of periodicity. A high contrast between the constituents of microstructured multiphase materials can lead to unusual wave scattering and absorption, which are interesting and relevant from a physical viewpoint, for instance, in the case of crystals with defects. We present a computational multiscale method in the spirit of the Localized Orthogonal Decomposition and provide its rigorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…However, the Helmholtz equation (with positive coefficients), was analyzed in [16,29,31]. In particular, it is shown that the corrector problems are well-posed under a resolution condition on because the 2 -perturbation in the Gårding inequality can be absorbed for functions in the kernel due to the property (3.5) of .…”
Section: Weak T-coercivitymentioning
confidence: 99%
See 3 more Smart Citations
“…However, the Helmholtz equation (with positive coefficients), was analyzed in [16,29,31]. In particular, it is shown that the corrector problems are well-posed under a resolution condition on because the 2 -perturbation in the Gårding inequality can be absorbed for functions in the kernel due to the property (3.5) of .…”
Section: Weak T-coercivitymentioning
confidence: 99%
“…Proof. The well-posedness of (5.3) follows from an inf-sup condition on , (see [31] for instance). This directly yields quasi-optimality and the error estimate (5.4), where we refer to Chapter 2 of [24] for details.…”
Section: Localized Correctorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main contribution of this article are the presentation and numerical analysis of multiscale methods in the spirit of the LOD for the Helmholtz equation with Kerr-type nonlinearity. Various works have successfully applied the LOD to wave propagation problems such as the wave equation [AH17,MP19], the Helmholtz equation with constant [GP15,Pet17] and spatially varying coefficients [BGP17,PV20] as well as time-harmonic Maxwell's equations [GHV18,Ver17,HP20]. Besides dealing with multiscale coefficients, the LOD can also reduce the well-known pollution effect for the linear Helmholtz equation [GP15,Pet17].…”
Section: Introductionmentioning
confidence: 99%